Characterization of ferroptosis in murine models of hemochromatosis. Issue 2 (16th May 2017) - Wang, Hao; An, Peng; Xie, Enjun; Wu, Qian; Fang, Xuexian; Gao, Hong; Zhang, Zhuzhen; Li, Yuzhu; Wang, Xudong; Zhang, Jiaying; Li, Guoli; Yang, Lei; et al.
Abstract : Ferroptosis is a recently identified iron‐dependent form of nonapoptotic cell death implicated in brain, kidney, and heart pathology. However, the biological roles of iron and iron metabolism in ferroptosis remain poorly understood. Here, we studied the functional role of iron and iron metabolism in the pathogenesis of ferroptosis. We found that ferric citrate potently induces ferroptosis in murine primary hepatocytes and bone marrow–derived macrophages. Next, we screened for ferroptosis in mice fed a high‐iron diet and in mouse models of hereditary hemochromatosis with iron overload. We found that ferroptosis occurred in mice fed a high‐iron diet and in two knockout mouse lines that develop severe iron overload ( Hjv –/– and Smad4 Alb/Alb mice) but not in a third line that develops only mild iron overload ( Hfe –/– mice). Moreover, we found that iron overload–induced liver damage was rescued by the ferroptosis inhibitor ferrostatin‐1. To identify the genes involved in iron‐induced ferroptosis, we performed microarray analyses of iron‐treated bone marrow–derived macrophages. Interestingly, solute carrier family 7, member 11 ( Slc7a11 ), a known ferroptosis‐related gene, was significantly up‐regulated in iron‐treated cells compared with untreated cells. However, genetically deleting Slc7a11 expression was not sufficient to induce ferroptosis in mice. Next, we studied iron‐treated hepatocytes and bone marrow–derived macrophages isolated from Slc7a11 –/– mice fed a high‐iron diet. Conclusion: We found that iron treatment induced ferroptosis in Slc7a11 –/– cells, indicating that deleting Slc7a11 facilitates the onset of ferroptosis specifically under high‐iron conditions; these results provide compelling evidence that iron plays a key role in triggering Slc7a11‐mediated ferroptosis and suggest that ferroptosis may be a promising target for treating hemochromatosis‐related tissue damage. (Hepatology 2017;66:449–465).